Comparison between high dose hyperbaric Bupivacaine (12.5 mg) alone versus low dose hyperbaric Bupivacaine (7.5 mg) with Fentanyl (25 µg) in spinal anaesthesia for inguinal hernia surgery - Kotwani, Manish B.; Rupwate, Kanchan; Shivananda, Prashanth; Magar, Jyoti (International Journal of Clinical Trials, 2016)
Background: For performing inguinal hernia surgeries, giving spinal anesthesia is a well known technique as it easy and provides fast onset, effective sensory and motor blockade in an awake patient. Now-a-days Bupivacaine is gaining importance as an effective spinal anaesthetic agent in combination with opioid analgesic Fentanyl to reduce the postoperative pain and side effects associated with surgery. This study aims to compare the effectiveness of intrathecal Bupivacaine alone versus combination of Bupivacaine with Fentanyl. Methods: The study designed was a prospective, randomized, double blinded comparative study. Patients were randomly divided into two groups of 25 each. Group B received hyperbaric intrathecal Bupivacaine 12.5 mg and Group BF received diluted hyperbaric intrathecal Bupivacaine 7.5 mg and Fentanyl 25 µg for spinal anesthesia . Parameters like sensory and motor block were assessed. Side effects produced during perioperative and postoperative period were observed and noted. Satisfactory criteria by the surgeons and patients were considered. Results: The time taken to attain surgical anesthesia and peak sensory levels in minutes was statistically significant in Group B compared to Group BF. Due to higher dose of Bupivacaine, it was observed that degree of motor blockade is also higher in group B when compared to group BF. The incidence of hypotension, nausea, vomiting and hypothermia are significantly higher in group B due to high dose of Bupivacaine. The surgeons and patients satisfaction was good in both the groups. Conclusions: Low dose Bupivacaine in combination with Fentanyl is safe and effective alternative for spinal anesthesia for inguinal herniorrphaphy as compared to conventional high dose Bupivacaine alone.